THE ROLE OF GYMNASTICS IN THE PHYSICAL DEVELOPMENT OF CHILDREN AND ADOLESCENTS - Robilova Sharofat; Abdumalikova Nigora (Journals Park Publishing, 2023)
The article deals with the issues of introducing into the training process the developed differentiated author's methodology for testing the motor and technical training of girls specializing in rhythmic gymnastics to determine their prospects at the initial stage of sports improvement.
Keywords: differentiated methodology, training process, criterion, testing, motor qualities, technical training, complexly coordinated motor acts.